2014
DOI: 10.15171/ijhpm.2014.83
|View full text |Cite
|
Sign up to set email alerts
|

Preventing injuries in workers: the role of management practices in decreasing injuries reporting

Abstract: Background: Researchers have found that management safety practices may predict occupational injuries and psychological distresses in the workplace. The present study examined the perception of management safety practices related to injuries reporting and its dimensions among workers of Isfahan Steel Company (ESCO). Methods: A self-administered anonymous survey was distributed to 189 workers. The survey included demographic factors, management safety perception, injuries reporting and its components (physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In recent years, the impact of organizational climate on healthcare worker's occupational injuries has been increasingly studied (Braithwaite et al, 2017). To our knowledge, poor safety climate as an important influence on occupational injuries among healthcare workers has been studied (Amponsah-Tawiah & Mensah, 2016;Kiani & Khodabakhsh, 2014). Moreover, improving the safety climate of hospitals offers numerous benefits (Aljabri et al, 2020;Oh et al, 2006;Sekimoto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the impact of organizational climate on healthcare worker's occupational injuries has been increasingly studied (Braithwaite et al, 2017). To our knowledge, poor safety climate as an important influence on occupational injuries among healthcare workers has been studied (Amponsah-Tawiah & Mensah, 2016;Kiani & Khodabakhsh, 2014). Moreover, improving the safety climate of hospitals offers numerous benefits (Aljabri et al, 2020;Oh et al, 2006;Sekimoto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This was mainly determined by practical obstacles such as inappropriate or broke equipment, and the management’s expectations that production levels should be maintained constant even if staffing was low. Kiani and Khodabakhsh ( 77 ) found evidence for an association between employees’ perception of management safety practices and the tendency to report injuries in the Iranian steel industry. Finally, a poor access to mitigation resources has been shown to relate to the risk of workplace injury ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beus and colleagues (2010) found that perceived management commitment to workplace safety is an important determinant of workplace injury prevention. Kiani and Khodabakhsh (2014) noted that supervisors are seen as one of the key elements in health and safety management at the workplace in ensuring safety compliance and preventing worker injuries. In addition, Yule, Flin, and Murdy (2006) demonstrated that employees conformed to safety rules and procedures when they perceived that the action of their supervisor were fair and consistent with organization safety policies.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Commitment to clarifying and communicating supervisor and employee responsibilities can help foster a climate of safety and is likely to encourage both groups to play a more active role in ensuring workplace safety (Kiani & Khodabakhsh, 2014). Training that incorporates supervisors as well as work teams or work units may provide for better communication and understanding of safety protocols and responsibilities (Weaver et al, 2013).…”
Section: Implications For Occupational Health Practicementioning
confidence: 99%